Typical and Atypical Imaging Findings of Hepatocellular Carcinoma on Multiphasic MDCT Scan in Histologically Proved Cases - Umakant Prasad; Deepak Kumar; Rashmi Rani Bharti; Sanjay Kumar Suman; Aishwerya Singh; Ravikant Kumar (Thieme Medical and Scientific Publishers Pvt. Ltd., 2022)
Objective The purpose of this study was to find out the incidence of typical and atypical radiological imaging findings of hepatocellular carcinoma (HCC) on multiphase multidetector computed tomography (MDCT) scans in histologically proven cases. Materials and Methods A multiphase computed tomography study of 73 patients with histologically proven HCC was evaluated by a radiologist. Our multiphasic protocol was composed of precontrast, arterial, portal, and delayed venous phases. The reviewers analyzed the CT images for tumor size, enhancement patterns of HCC in different phases, relative timing of washout, internal cystic changes, and presence of dysmorphic intratumoral vessel aneurysms or arteriovenous shunt. Results Most of the cases (95.9%) showed typical enhancement patterns in MDCT, i.e., enhancements in the arterial phase with the portal or delayed venous phase contrast washout. Three cases (4.9%) out of 73 HCC showed enhancements in the portal phase and washout in the delayed venous phase. Seven cases out of total 73 HCC (9.5%) patients showed heterogeneous enhancements in both arterial and portal phases and contrast washout in the delayed venous phase. Venous thrombosis was noted in about 44 cases (60%) out of total 73 patients, in which portal vein thrombosis was more common than hepatic veins/inferior vena cava. Conclusion Most of the HCC show typical enhancement patterns, i.e., heterogeneous enhancements in the arterial phase and washout in the portal venous phase when we use MDCT. These findings are higher than those described previously. However, in our study, the main difference with MDCT was lower frequency of intratumoral pseudoaneurysm and bile duct invasion, and intratumoral fat and calcification (atypical character of HCC) were not found which were rare findings in previous study.